Hydrogen sulfide and carbon monoxide tolerance in bacteria - Mendes, Sofia S. (2021)
Funding Information: This work was financially supported by Funda??o para a Ci?ncia e Tecnologia (Portugal) through fellowship PD/BD/148006/2019 (SSM), PTDC/SAU-INF/29313/2017 grant, and R&D unit LISBOA-01-0145-FEDER007660 (MostMicro) cofounded by FCT/MCTES and FEDER funds under the PT2020 Partnership Agreement. This work was partially supported by PPBI?Portuguese Platform of BioImaging (PPBI-POCI-01-0145-FEDER-022122) co-funded by national funds from OE? ?Or?amento de Estado? and by European funds from FEDER??Fundo Europeu de Desenvolvimento Regional?. We also acknowledge funding from the European Union?s Horizon 2020 research and innovation program under grant agreement No. 810856. Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.